Limits to substitution between ecosystem services and manufactured goods and implications for social discounting - Moritz A. Drupp (Kiel University, Department of Economics, 2016)
This paper examines implications of limits to substitution for estimating substitutability between ecosystem services and manufactured goods and for social discounting. Based on a model that accounts for a subsistence requirement in the consumption of ecosystem services, we provide empirical evidence on substitution elasticities. We find an initial mean elasticity of substitution of two, which declines over time towards complementarity. We subsequently extend the theory of dual discounting by introducing a subsistence requirement. The relative price of ecosystem services is non-constant and grows without bound as their consumption declines towards the subsistence level. An application suggests that the initial discount rate for ecosystem services is more than a percentage-point lower as compared to manufactured goods. This difference increases by a further half percentage-point over a 300-year time horizon. The results underscore the importance of considering limited substitutability in long-term public project appraisal.
Keywords: Q01; Q57; H43; D61; D90; 330; Limited substitutability; Dual discounting; Ecosystem services; Subsistence; Project evaluation; Sustainability